2009
DOI: 10.1098/rspb.2009.0828
|View full text |Cite
|
Sign up to set email alerts
|

Synchronization of spontaneous eyeblinks while viewing video stories

Abstract: Blinks are generally suppressed during a task that requires visual attention and tend to occur immediately before or after the task when the timing of its onset and offset are explicitly given. During the viewing of video stories, blinks are expected to occur at explicit breaks such as scene changes. However, given that the scene length is unpredictable, there should also be appropriate timing for blinking within a scene to prevent temporal loss of critical visual information. Here, we show that spontaneous bl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

14
141
0
3

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 164 publications
(158 citation statements)
references
References 30 publications
14
141
0
3
Order By: Relevance
“…It was therefore not possible to determine whether blinks while driving also tend to occur during implicit or explicit attentional breaks, as previously noted. 14,15 In summary, the present findings give support to recent research describing spontaneous blinking as a complex mechanism regulated by a ''central pacemaker'' which, in turn, is modulated by, among other factors, the cognitive and attentional demands of the visual task at hand and the onset of large amplitude gaze shifts. Our results suggest that, when high cognitive demands are accompanied by an increase in the number of large amplitude saccades, the contribution of the latter is more significant in determining spontaneous blink rate.…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…It was therefore not possible to determine whether blinks while driving also tend to occur during implicit or explicit attentional breaks, as previously noted. 14,15 In summary, the present findings give support to recent research describing spontaneous blinking as a complex mechanism regulated by a ''central pacemaker'' which, in turn, is modulated by, among other factors, the cognitive and attentional demands of the visual task at hand and the onset of large amplitude gaze shifts. Our results suggest that, when high cognitive demands are accompanied by an increase in the number of large amplitude saccades, the contribution of the latter is more significant in determining spontaneous blink rate.…”
Section: Discussionsupporting
confidence: 72%
“…14,15 Indeed, while reading, for example, blinks tend to be timed to occur at the punctuation breaks present within the text. 15 Similarly to blinks, saccade eye movements are also accompanied by a suppression of visual input, thus explaining the visual stability that persists during ocular movements, despite the corresponding displacement of the image on the retina.…”
mentioning
confidence: 99%
“…6;2015 E-Learners were deal with the computer and the virtual environment that was also providing an attractive atmosphere to engage in this experiment. That might be a reason for decrease of the eye blink during the e-Learning activities since they keep the eyes opened to catch the critical attractive visuals while reducing the blink to avoid the loose of attractive visuals (Nakano, Yamamoto, Kitajo, Takahashi, & Kitazawa, 2009). Although e-Learning session was based on the problem, the stress might be decreased due to the shared responsibility of a group activity.…”
Section: Wwwccsenetorg/iesmentioning
confidence: 99%
“…Although e-Learning session was based on the problem, the stress might be decreased due to the shared responsibility of a group activity. Less cognitive load or low stress, rich critical information or attractive visual information and engage in a computer or visual equipment are some reasons for a low frequency of eye blink (Holland & Tarlow, 1975;Nakano et al, 2009). E-Learners conducted problem based learning in this experiment and it was basically based on the communication among the participants.…”
Section: Wwwccsenetorg/iesmentioning
confidence: 99%
“…Moreover, these studies showed that when we perceive an event or scene segmentation in visual streams, brain activity (Hasson, Nir, Levy, Fuhrmann, & Malach, 2004;Kurby & Zacks, 2008), pupil diameter (Beatty & LuceroWagoner, 2000), and the frequency of saccades and eye blinks are affected (Swallow & Zacks, 2004;Nakano, Yamamoto, Kitajo, Takahashi, & Kitazawa, 2009). Previous studies reported the automatic synchronization of physiological activities with the viewing of a specific scene or boundary of scene change.…”
mentioning
confidence: 99%